Analysis of Destita’s Political Communication in Building Personal Branding at the Regional Representative Council of the Republic of Indonesia (DPD RI) - Ramadhan Dewantara; Anis Endang SM; Yanto Yanto (Journal of Multidisciplinary Research, 2026)
Personal branding is the process of building a unique, strong, and relevant self-image in the public’s mind. In modern political contexts, personal branding serves as a strategic tool to shape public perception, trust, and voter loyalty, particularly through social media platforms. This study aims to analyze Destita Khairilisani’s political communication strategy in building her personal branding as a member of the Regional Representative Council of the Republic of Indonesia (DPD RI) through her Instagram account @destitabengkulu, using Peter Montoya’s eight laws of personal branding as the analytical framework. This research employs a qualitative descriptive approach with a single case study strategy within a constructivist paradigm. Data were analyzed using content analysis of Instagram posts from December 2025 to January 2026, supported by library research. The findings indicate that The Law of Specialization serves as the primary pillar in constructing Destita’s image as a “Technocrat-Pharmacist” and doctoral academic with expertise in health and education. This specialization is reinforced by solution-oriented leadership, an inclusive personality, consistent visual differentiation, and sustained digital visibility. The integration of professional competence, authentic character, and message consistency shapes her image as a “Doctor for Regional Problems,” aligning with the needs of the Bengkulu community. The study concludes that specialization, consistency, and moral values are key factors in building political trust and legitimacy in the digital communication era.